Strategi Manajemen Usaha Kecil Pada Sentra IKM Jawet Pahari Hapakat Dalam Meningkatkan Daya Saing Produk Lokal - Rahman, Rahman; Alexandro, Rinto; Fithra Ramadian (FKIP, Universitas Palangka Raya, 2025)
This research aims to develop lepironia articulata based sustainable product innovation through a green entrepreneurship education approach for students of SMKN 4 Palangka Raya City.lepironia articulata is a typical peat swamp plant in Central Kalimantan that has great potential as an environmentally friendly raw material to replace disposable plastic-based products. The problems faced are the low creative utilization of purun and the lack of knowledge of students about green entrepreneurship. Therefore, this research was designed to improve students' entrepreneurial skills by emphasizing creativity, sustainability, and environmental awareness. The research method used a descriptive qualitative approach with stages of observation, training, and assistance in making innovative purun products. Data were collected through interviews, documentation, and observation of student activities. The results showed that green entrepreneurship education was able to encourage students to produce innovative products, such as purun-based bags, containers, and accessories that have economic value and are environmentally friendly. In addition, this activity fosters an attitude of environmental care, improves entrepreneurial skills, and strengthens students' creative and independent characters. Thus, this research makes a real contribution in building a young generation that is competitive, environmentally sound, and supports sustainable economic development in Central Kalimantan